A solitary primary subcutaneous hydatid cyst in the thigh: a case report - AE., Ahmed; ., Taki-Eldin (International Surgery Journal, 2016)
Hydatid disease is a parasitic infestation caused by Echinococcusgranulosus. It occurs frequently in liver and lung. Hydatid disease of the soft tissue is uncommon. In this paper, we report a case of a primary subcutaneous hydatid cyst in the thigh. We report a case of a 45-year-old female who presented to our hospital with a painless subcutaneous mass in the medial aspect of the right thigh for one year. Computed tomography scan demonstrated a subcutaneous cystic lesion close to adductor magnus muscle. The diagnosis of hydatid cyst was suspected peroperatively, complete surgical excision of the mass was done and the patient had an uneventful post-operative recovery. The suspected diagnosis was confirmed by histopathological examination. This case shows that hydatid cyst should be considered in the differential diagnosis of any cystic mass at different anatomical sites, especially in endemic regions. Total excision of the cyst with an intact wall remains the mainstay of treatment.